Assessment of the Breakaway Torque at the Posterior Pelvic Ring in Human Cadavers. (2nd November 2015) - Bastian, Johannes Dominik; Bergmann, Mathias; Schwyn, Ronald; Keel, Marius Johann Baptist; Benneker, Lorin Michael
ABSTRACT: Purpose : To enhance the diminished screw purchase in cancellous, osteoporotic bone following the fixation of posterior pelvic ring injuries by iliosacral screws an increased bone-implant contact area using modificated screws, techniques or bone cement may become necessary. The aim of the study was to identify sites within the pathway of iliosacral screws requiring modifications of the local bone or the design of instrumentations placed at this site. Materials and Methods : The breakaway torque was measured mechanically at the iliosacral joint ("ISJ"), the sacral lateral mass ("SLM") and the center of the S1 ("CS1"), at a superior and an inferior site under fluoroscopic control on five human cadaveric specimens (3 female; mean age 87 years, range: 76–99) using the DensiProbe™Spine device. Results : The measured median (range) breakaway torque was 0.63 Nm (0.31–2.52) at the "iliosacral joint", 0.14 Nm (0.05–1.22) at the "sacral lateral mass", 0.57 Nm (0.05–1.42) at the "S1 center." The "sacral lateral mass" breakaway torque was lower than compared to that at the "iliosacral joint" ( p < .001) or "S1 center" ( p < .001). The median (range) breakaway torque measured at all superior measurement points was 0.52 Nm (0.10–2.52), and 0.48 Nm (0.05–1.18) at all inferior sites. The observed difference was statistically significant ( p < .05). Conclusions : The lateral mass of the sacrum provides the lowest bone quality for implant anchorage. Iliosacral screws should be placed as superior as safely possible, should bridge the iliosacral joint and may allow for cement application at the lateral mass of the sacrum through perforations.